Biomechanics of surfing: Development and validation of an instrumented surfboard to measure surfboard kinetics - Lestrade, K.; Guerard, S.; Lanusse, P.; Viot, P. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate the different relations between the actions of a surfer and the kinematic behaviour of his surfboard. An instrumented surfboard has been designed with a force platform synchronized with an inertial measurement unit and acquisition system. An experimental campaign has been carried out in situ, where different waves have been surfed to validate the device. Results revealed that measured efforts of the surfer and kinematics of his surfboard are consistent regarding the expected behaviour. Instrumented surfboards will help coaches by giving them a new performance analysis tool. It will also provide an experimental database for the development of numerical models about interactions Surfer/Surfboard/Wave.